Occurrence of arbuscular mycorrhizal fungi in Emblica officinalis Gaertn. and Zizyphus mauritiana Lamk. - A. SHUKLA*; A. JHA, A. KUMAR, S. HASHMI (Indian Phytopathology, 2009)
Studies on occurrence of arbuscular mycorrhizal (AM) fungi in different varieties of Aonla (Emblica officinalis Gaertn.) and Ber (Zizyphus mauritiana Lamk.) and two soil types (black and red) were carried out. In Aonla, maximum colonization index was recorded in variety Krishna (22.7%) followed by Kanchan (20.0%), Chakaiya (16.5%) and NA-7 (16.3%). Spore counts in rhizosphere of different Aonla varieties were at par which ranged from 9 to 13 per 100 g soil. In Ber, colonization index of different varieties (Banarasi Karaka, Gola and Seo), its Desi plants and three wild relatives (Ghot, Jharberi and Makor) were at par. Maximum spore count was recorded in Banarsi Karaka (30 per 100 g soil), followed by Ghot (29 per 100 g soil), Gola (26 per 100 g soil), Jharberi (22 per 100 g soil) and Makor (21 per 100 g soil). Among different seasons, maximum colonization index and spore counts were recorded during rainy season in both fruit crops. Five speciesbelonging to three genera namely, Glomus, Acaulospora and Gigaspora were common. Maximum total spore count was recorded for Glomus followed by Acaulospora and Gigaspora. Among soil types, mean colonization index was significantly higher in black soil and better sporulation was recorded in red soil. Differences in sporulation in black and red soils were more pronounced in Acaulospora than Glomus. Soil moisture and soil surface temperatures recorded in black soil were more than red soil. However, soil surface temperature did not affect the sub soil temperatures in the root zone at 10 cm depth which were at par in studied soil types.